FAKTOR PENUNJANG PERTUNJUKAN MUSIK: INPUT, PROSES, DAN OUTPUT - Jatmika, Ovan Bagus (Journal of Music Science, Technology, and Industry, 2020)
This research examines the supporting factors in improving the quality of musical performances. The method used is qualitative and the research data are found through library research. The author concludes that a performance is considered to have ideal conditions if it involves three elements that support each other in the process towards the end of the musical execution on the stage, namely input, process, and output. These three elements (input, process, and output) are expected to improve the quality of the performance. The intended form of quality improvement is the formation of two-way communication or dialogue between the player and the audience. The player conveys the musical content of their interpretation of the work being played, while the audience responds to the standard measure of musical, visual and gestural norms that they have / believe in. Keywords: musical stimuli, musical emotions, learning motivation, exercise effectiveness, musical memory.